The Self-Concept of Students with Non-Suicidal Self Injury (NSSI) Behavior - bila, Salsa; Pello, Shela Christine; Benu, Juliana Marlin Yustrianti; Anakaka, Dian Lestari (Universitas Nusa Cendana, 2025)
Students are often recognized as individuals who frequently face various challenges, both physical and psychological. Those who experiencing psychological distress but unable to express their emotions are at risk of engaging in Non-Suicidal Self-Injury (NSSI) behaviors. This study aims to explore the self-concept of students who engage in NSSI in Kupang City. A qualitative research design with a phenomenological approach was employed. The research involved four female student informants selected through purposive and snowball sampling techniques. Data were collected using semi-structured interviews. The findings revealed five main themes: real-self, factors contributing to NSSI, social relationships, social support, and moral values. It is recommended that students develop self-acceptance, view the past as a source of learning, recognize NSSI triggers, and avoid sharp objects. Students are also encouraged to engage in productive activities such as exercising, pursuing hobbies, or taking leisurely walks, as well as joining communities that promote mental health.